„Potworna zdrada”. O źródłach kontrowersyjności adaptacji Doliny Issy - Kaniecki, Przemysław (Poznańskie Studia Polonistyczne. Seria Literacka, 2012)
The author attempts to identify the origins of the famous argument between Miłosz and Konwicki about the film adaptation of Dolina Issy. Konwicki created a film which, although it is an adaptation of the novel, clearly belongs to his own creative output, focused on axiological uncertainty after The Second World War. Konwicki’s work is a record of a quest for enduring points of reference, a quest conducted with realisation that such points cannot be found by a person who feels lost in the modern world. Such a world-view was not acceptable for Miłosz, and it is difficult to expect that the poet would accept an adaptation of his novel created from such a point of view.